Seed Quality of Velvet Bean Seeds (Mucuna pruriens L. Dc) in Western Kenya - Diop , Mamie Souadou; Ochuodho , Julius O.; Maina , Faith N. W.; Rop , Nicholas K. (African Journal of Education,Science and Technology (AJEST), 2023)
Farmers in Bungoma County are actively involved in velvet bean (Mucuna pruriens L. DC) production due to its multiple uses. It can be used to improve soil fertility, nutrition, drought tolerance, pest and disease tolerance, food security and medicinal. Variation in seed characteristics has been reported to be useful for crop improvement programs. However, production of quality seed is a challenge for farmers in this county. The purpose of this research was to investigate the quality of velvet bean seed. Four types of velvet bean seeds were obtained from farmers during a survey. Morphological variability in seed characteristics like seed coat color, hilum color, seed length, width and thickness (IBPGR descriptor) were evaluated in four replications of 50 seeds each. Fifty seeds replicated 3 times were used to determine the electrical conductivity (EC) for each seed type. Germination test of these seeds was laid out in a CRD. To investigate the dynamics and rates of imbibition, thirty seeds replicated 3 times for each seed type were subjected to temperatures of 20, 25, 30, 30/20°C and in ambient condition during a germination test. Data were subjected to analysis of variance (ANOVA) using GENSTAT software release 14.1 and the mean separations was done using least significant difference (LSD) at 5%. Pearson correlation coefficient was used to analyze seed traits of the morphotypes. Germination percentage data was analyzed using Microsoft Office (Excel) V.2013. There were significant differences (P ≤ 0.05) among seed types in all seed traits measured except seed coat thickness. White seed type recorded a lower electrical conductivity (more vigorous), higher final germination percentage, higher speed of germination index and higher imbibition rate at 30°C for both substratum (sand and filter paper) than other seed types. This study therefore recommends that the barriers to germination in dark colored seed types need to be addressed by seed scientists to improve velvet bean seed quality at farm level hence increase the production. Further study can be done on genetic and physiological properties of velvet bean black seed type in order to improve its germination capacity.